Understanding the Need of Regular Staff Training: A Study of Private Hospitals in India - Ashwini Anil; Noor un Nisa (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: Employee training sometimes falls to the bottom of the list of priorities while managing a busy health and social care service due to the abundance of issues to take into account. The greatest human resources may be developed and retained via training, which also offers new skills and information. The entire training practices in private hospitals in India were to be evaluated in this study. The research primarily examines how training affects worker performance, organizational commitment, and the standard of healthcare services. Methodology: A questionnaire was used to gather primary data, and one item was left open-ended to allow for further exploration of the subject. Findings: The study’s results revealed that although employees occasionally receive training, only a small percentage of them think it is of a high enough caliber to have an impact on both their personal life and the company’s. Additionally, they didn’t think that the training had increased their dedication to the organization or changed the way they thought or behaved. They contend that variables other than their connection with their employers have a bigger role in determining their retention rate at a company. Employees acknowledged that certain abilities had improved, which suggests that hospitals utilize a set of broad training techniques that are not altered to meet specific hospital demands. Not every employee said that assessments are conducted on a regular basis. Employees are not involved in the creation of training modules, and they do not believe that training and evaluations have made them stand out for both themselves and their employer. Given that the healthcare industry is always changing, having a professional, educated, and adaptive personnel should always be a top concern. For anybody working in the healthcare industry, training is a must, not just a nice-to-have. Implications/Novel Contribution: The hospitals may utilize these findings to enhance their training initiatives and get the most out of them.